2021
DOI: 10.3390/pharmaceutics13010091
|View full text |Cite
|
Sign up to set email alerts
|

New Nanoparticle Formulation for Cyclosporin A: In Vitro Assessment

Abstract: Cyclosporin A (CsA) is a molecule with well-known immunosuppressive properties. As it also acts on the opening of mitochondrial permeability transition pore (mPTP), CsA has been evaluated for ischemic heart diseases (IHD). However, its distribution throughout the body and its physicochemical characteristics strongly limit the use of CsA for intravenous administration. In this context, nanoparticles (NPs) have emerged as an opportunity to circumvent the above-mentioned limitations. We have developed in our labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…These results were concordant with our previous work done with H9c2, (cardiomyoblast cell line) and MCEC (Mouse Cardiac Endothelial Cells), where accumulation of fluorescent SQ-based NPs was strongly detected after 18 h of incubation [ 25 ]. In a previous work, our group demonstrated that the LDL Receptor was involved in SQAd NPs internalization by HepG2 cells [ 26 ].…”
Section: Resultssupporting
confidence: 93%
“…These results were concordant with our previous work done with H9c2, (cardiomyoblast cell line) and MCEC (Mouse Cardiac Endothelial Cells), where accumulation of fluorescent SQ-based NPs was strongly detected after 18 h of incubation [ 25 ]. In a previous work, our group demonstrated that the LDL Receptor was involved in SQAd NPs internalization by HepG2 cells [ 26 ].…”
Section: Resultssupporting
confidence: 93%
“…More recently, new formulations using PLGA-, squalene- or lipid-based nanoparticles were developed to increase cell permeability of the therapeutic CsA but no preclinical study was yet performed ( 126 128 ). Also, combined administration of polymeric nanoparticles encapsulating CsA or pitavastatin (organic compound) targeting mPTP opening and monocyte-mediated inflammation, respectively, has been reported to be more efficient than a single administration of encapsulated CsA ( 129 ) even if CsA impacts per se the immune response after myocardial IR ( 130 ).…”
Section: Therapeutic Peptides Reducing Apoptosis To Treat Mirimentioning
confidence: 99%
“…Cyclosporine A (CsA) is an immunosuppressive drug that can inhibit the abnormal immune response of the body and is widely used in clinical practice to prevent and treat transplant rejection, diseases caused by hypersensitivity reactions, and autoimmune diseases, etc. [1][2][3][4][5][6][7][8][9] However, the blood concentration of CsA is closely related to the degree of immunosuppression and hepatic and renal toxicity, showing great intraindividual and interindividual pharmacokinetic differences and a relatively narrow therapeutic window. [10][11][12] Therefore, blood concentration must be monitored promptly during clinical application to ensure the therapeutic effect while minimizing rejection reactions and toxic side effects.…”
Section: Introductionmentioning
confidence: 99%